A Test of the Self-Consistency Theory of the Job Performance-Job Satisfaction Relationship - López, Elsa Mallor (Academy of Management Journal, 1982)
The employment of multidimensional measures of self-esteem, job performance, and job satisfaction on separate samples of male and female employees was found to enhance the self-consistency prediction that self-esteem moderates the job performance-job satisfaction relationship. Specific dimensions of self-esteem interacted with job satisfaction factors in different ways for males and females.